ANALYSIS OF FACTORS AFFECTING THE INCOME OF CIRCULAR MIGRANT WORKERS IN DENPASAR CITY - Moh. Toha Alimuddin Nadir; Ida Ayu Meisthya Pratiwi (Adisam Publisher, 2025)
Denpasar is one of the cities with the fastest population growth in Bali. The availability of sufficient employment opportunities, economic centralization and the availability of educational facilities have made many people interested in making Denpasar City a migration destination. The aims of this research are: 1) to analyze the influence of the number of family dependents, working hours, education and work experience simultaneously on the income of circular migrant workers in Denpasar City, 2) to analyze the influence of the number of family dependents, working hours, education and work experience partially on the income of circular migrant workers in Denpasar City. This research was conducted in Denpasar City, Bali Province in 2024, using primary and secondary data, observation data collection methods, structured interviews, etc. were carried out. The sampling method used was a non- probability sampling method with a quota sampling technique combined with accidental sampling. The data analysis techniques used are descriptive statistical analysis test, classical assumption test, multiple linear regression analysis test, F test and t test.The number of respondents to this research was 120 circular migrant workers in Denpasar City. Factors include the number of family dependents, working hours, education and work experience. The results of this research show that: 1) The factors of number of family dependents, working hours, education and work experience simultaneously influence the income of circular migrant workers in Denpasar City. 2) The factors of number of family dependents, working hours, education and work experience partially have a positive effect on the income of circular migrant workers in Denpasar City.